The effect of Preventive Exercises According to the Application of Muscle and Motion on the Development of the Most Important Physiological Variables Associated with High Load Injuries and Muscular Soreness in Handball Players - Samer Mahdi Muhammad Saleh; Ahmed Yousif Miteb; Walead Ahmed Alrahahleh (Indian Journal of Forensic Medicine & Toxicology, 2021)
Handball has become practiced in the most countries of the world still suffer from obstacles that impedetheir development to achieve the better, and one of those obstacles is sports injury, researchers noticed thehigh incidence of sports injuries among handball players in recent sports seasons and the lack of interest ofcoaches in the physical preparation for the prevention of frequent injuries among handball players, The aimsof the research were preparing preventive exercises according to the (muscle and motion) application, andidentifying the effect of preventive exercises on the most important physiological variables associated withhigh load injuries and muscular soreness for handball players. Researchers used the experimental methodto solve the problem of the research by implementation of the experimental design using pre-test and posttest.The research’s community consisted of 20 players from the Karbala Sports Club, they were dividedinto two equal groups (experimental and control groups). The researchers carried out pre-tests for playerswho represent the research community, Preventive exercises applied with members of the experimentalgroup for 8 weeks, 3 session per week, 24 training sessions, Post-tests were conducted for the experimentaland control groups, After collecting the data, it was processed statistically using the statistical packageSPSS, the researchers concluded that preventive exercises according to the application of MUSCLE andMOTION have a positive effect on developing the physiological variables associated with high load injuriesand muscular soreness for handball plyers player.